Analiza hitrosti v veleslalomu s pomočjo RTK GNSS - Supej, Matej (Šport (Ljubljana), 2023)
The purpose of this study was to develop a new method for synchronized and direct comparison of skiers’ speed along a track based on trajectory measurements utilizing Global Navigation Satellite System (GNSS). Nine skiers, members of the national youth team, were measured on the giant slalom course using a GNSS device. Times at each gate and times from gate to gate, as well as skiing speed, were calculated. Speeds were synchronized between each pair of adjacent gates based on the times at which the skier’s trajectory crossed the virtual plane at the gates. The analysis yielded a number of information related to the analysis of the skier’s time and speed. Moreover, it can be concluded from the results that the shortest time did not perfectly coincide with the highest speeds and vice versa, which is of utmost importance for an accurate analysis. In conclusion, the new methodology improves the analysis and can be used 1) in daily practice to compare skiers, 2) automatically with program routines and results can be obtained immediately after training session to enhance feedback.
Keywords: alpsko smučanje; biomehanika; čas; GLONASS; GPS; hitrost; navigacijski sistemi; šport; uspešnost